Endophytes of Brazilian Medicinal Plants With Activity Against Phytopathogens - Iantas, Jucélia; Savi, Daiani Cristina; Schibelbein, Renata da Silva; Noriler, Sandriele Aparecida; Assad, Beatriz Marques; Dilarri, Guilherme; Ferreira, Henrique; Rohr, Jürgen; Thorson, Jon S.; Shaaban, Khaled A.; Glienke, Chirlei (Frontiers in Microbiology, 2021)
Plant diseases caused by phytopathogens are responsible for significant crop losses worldwide. Resistance induction and biological control have been exploited in agriculture due to their enormous potential. In this study, we investigated the antimicrobial potential of endophytic fungi of leaves and petioles of medicinal plants Vochysia divergens and Stryphnodendron adstringens located in two regions of high diversity in Brazil, Pantanal and Cerrado, respectively. We recovered 1,304 fungal isolates and based on the characteristics of the culture, were assigned to 159 phenotypes. One isolate was selected as representative of each phenotype and studied for antimicrobial activity against phytopathogens. Isolates with better biological activities were identified based on DNA sequences and phylogenetic analyzes. Among the 159 representative isolates, extracts from twelve endophytes that inhibited the mycelial growth (IG) of Colletotrichum abscissum (≥ 40%) were selected to expand the antimicrobial analysis. The Minimum Inhibitory Concentrations (MIC) of the extracts were determined against citrus pathogens, C. abscissum, Phyllosticta citricarpa and Xanthomonas citri subsp. citri and the maize pathogen Fusarium graminearum. The highest activity against C. abscissum were from extracts of Pseudofusicoccum stromaticum CMRP4328 (IG: 83% and MIC: 40 µg/mL) and Diaporthe vochysiae CMRP4322 (IG: 75% and MIC: 1 µg/mL), both extracts also inhibited the development of post-bloom fruit drop symptomns in citrus flowers. The extracts were promising in inhibiting the mycelial growth of P. citricarpa and reducing the production of pycnidia in citrus leaves. Among the isolates that showed activity, the genus Diaporthe was the most common, including the new species Diaporthe cerradensis described in this study. In addition, HPLC-UV / MS (high performance liquid chromatography, UV detection and mass spectrometry) and TLC (thin layer chromatography) analyzes of extracts produced by endophytes that showed high activity, indicated D. vochysiae CMRP4322 and P. stromaticum CMRP4328 as promising strains that produce new bioactive natural products. We report here the capacity of endophytic fungi of medicinal plants to produce secondary metabolites with biological activities against phytopathogenic fungi and bacteria. The description of the new species Diaporthe cerradensis, reinforces the ability of medicinal plants found in Brazil to host a diverse group of fungi with biotechnological potential.